LDP vs ODP for pancreatic adenocarcinoma: a case matched study from a single-institution. Issue 1 (December 2015) - Zhang, Miaozun; Fang, Ren; Mou, Yiping; Chen, Ronggao; Xu, Xiaowu; Zhang, Renchao; Yan, Jiafei; Jin, Weiwei; Ajoodhea, Harsha
Abstract Background Laparoscopic distal pancreatectomy (LDP) showed advantage of perioperation outcomes for benign and low-grade tumor of the pancreas. The application of LDP for pancreatic ductal adenocarcinoma (PDAC) didn't gain popular acceptance and the number of LDP for PDAC remains low. We designed a case-matched study to analysis the short- and long-term outcomes of the patients undergoing either Laparoscopic distal pancreatectomy or open distal pancreatectomy for PDAC. Method From 2003 to 2013, 17 patients were underwent LDP and 34 patients were underwent ODP for PDAC were matched by tumor size, age and body mass index (BMI). The two groups' demographic information, perioperative outcomes and survival data were compared. Results Baseline characteristics were comparable between the LDP and ODP groups. The intraoperative blood loss, first flatus, first oral intake and postoperative hospital stay were significantly less in LDP group than ODP group (50 ml vs400ml, P  = 0.000; 3d vs 4d, P  = 0.001; 3d vs 4d, P  = 0.003; 13d vs 15.5d, P  = 0.022). The mean operation time, overall postoperative morbidity and postoperative pancreatic fistula rates were similar in the two groups. 5 patients (29.4 %) in LDP group and 7 patients (20.6 %) in ODP group underwent extended resections. There were no significant differences in tumor sizes (3.5 cm vs 3.9 cm, P  = 0.664) and number of harvested lymph nodes (9 vs8P  = 0.534). The median overall survival for both groups was 14.0 months. Cox proportional hazards analysis showed extended resections, R1 resection, perineural invasion and tumor differentiation were associated with worse survival. Conclusion LDP is technically feasible and safe for PDAC in selected patients and the short-term oncologic outcomes were not inferior to ODP in this small sample study. However the long-term oncologic safety of LDP for PDAC has to be further evaluated by multicenter or randomized controlled trials.